Gel compound fabric for extracting water from air and preparation method of gel compound fabric
By loading hydrogel in fabrics, the fabric has low adsorption capacity and hygroscopic agent leakage problems in the field of air intake, and an air intake material with efficient hygroscopic and stable performance is achieved.
Patent Information
- Application Number
- CN202411396463.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing fabrics have problems with low adsorption capacity and leakage of hygroscopic agents in the field of air water intake, which cannot meet the needs of efficient hygroscopy.
By loading hydrogels in fabrics, the water storage and water retention properties of the hydrogels are utilized to enhance the moisture absorption and water retention properties of the material and prevent leakage of hygroscopic agents.
It achieves efficient moisture absorption, stable moisture absorption performance and high water storage capacity, reduces hygroscopic agent leakage, and improves the performance of air water intake materials.
Smart Images

Figure CN119507195A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbent-assisted water extraction, and in particular to a gel composite fabric for air water extraction and a preparation method thereof. Background Art
[0002] The atmosphere contains nearly 13 trillion tons of renewable fresh water, which is not restricted by geographical and climatic conditions and has become a highly anticipated emerging water source. Air-to-water technology converts gaseous water in the air into liquid fresh water. Using air-to-water technology to capture atmospheric water and use it for fresh water production can provide a sustainable water source for production, life, and agricultural development, which has important practical significance for arid areas and extreme water shortage scenarios.
[0003] Adsorbent-assisted water extraction is one of the most commonly used methods of existing air water extraction technology. It uses air water extraction materials to capture and enrich air moisture, and releases liquid water through desorption. It has the advantages of low cost and low equipment requirements. As a green and energy-saving emerging air water extraction technology, it has received widespread attention. The adsorbent used in air water extraction materials is the key and determines the fresh water production capacity. Commonly used adsorbents include metal organic framework materials (MOFs), hygroscopic salts such as CaCl2 and LiCl (CaCl2 and LiCl, etc.), silica gel, zeolite and other materials, but they have shortcomings such as high production cost and high desorption energy consumption.
[0004] Compared with conventional desiccant, fabrics have the characteristics of being designable, low cost, fast heat transfer, and light weight, and have great potential in the field of air water extraction. In particular, fabrics have a designable multi-level structure, which greatly enriches the diversity of fabric shapes and structures, can expand the contact area between fabric materials and the outside world, and improve water absorption and water transfer performance. However, the moisture absorption rate of fabrics themselves is limited, and cannot meet people's requirements for high moisture absorption of air water extraction materials. The limitation of low moisture absorption rate can be overcome by loading desiccant. However, the adsorption capacity of fabrics is low, the water storage performance is insufficient, and they cannot accommodate too much water; in addition, the fabrics and desiccant cannot form an effective combination, and the desiccant will leak during the moisture absorption process, causing the moisture absorption performance to decay, which limits their application in the field of air water extraction.
[0005] In view of the above shortcomings, conventional solutions mainly include ultraviolet light induced grafting method, plasma induced grafting method, etc. Functional functional groups are introduced into the fabric surface through light, heat, and high-energy rays to give the material high hygroscopic properties. However, due to the limitations of its own adsorption capacity, the water storage capacity of the material cannot be increased. In addition, the cumbersome operation and expensive equipment also limit its industrial production. However, compounding the fabric with a high water storage material through a simple process can effectively solve the drawbacks of conventional methods and prepare a composite fabric with efficient moisture absorption and water retention properties.
[0006] Therefore, developing a composite fabric water extraction product for air water extraction has important practical significance and application value. Summary of the invention
[0007] The purpose of the present invention is to solve the problems of low adsorption capacity and moisture absorbent leakage in the current fabric for air water extraction pointed out in the background technology, and to provide a gel composite fabric for air water extraction by means of the excellent water storage and water retention performance and dynamic coordination effect of hydrogel, and to provide a specific preparation method. The gel composite fabric prepared by this method has high efficiency in moisture absorption and water retention performance, stable moisture absorption performance, short synthesis route, and simple production process, so that low-cost air water extraction materials can be produced in large quantities.
[0008] Specifically, the present invention adopts the following technical solutions: A method for preparing a gel composite fabric for air water extraction, the preparation method specifically comprising the following steps: (1) First, 1.5-6.0 g of fabric (CF) is ultrasonically treated in a sodium hydroxide solution with a concentration of 20-40 g / L for 1-2 hours, and then the fabric is repeatedly washed with deionized water until it is neutral, and then dried at 70-80° C. for 8-12 hours to obtain a pretreated fabric; (2) 8.0-14.0 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (DMAPS), a desiccant and a cross-linking agent are mixed evenly in 100 mL of deionized water, and nitrogen is introduced into the mixture for 45-75 minutes to obtain a treated solution; (3) preparing a persulfate initiator aqueous solution, and spraying the persulfate initiator aqueous solution uniformly on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10-12 hours to obtain a persulfate initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) in the treatment solution obtained in step (2), reacting at 60-70° C. for 8-10 hours, thereby preparing a hydrogel composite fabric material with high moisture absorption and water retention performance.
[0009] Furthermore, the added amount of the desiccant is 10-50% of the mass of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.
[0010] Furthermore, the desiccant is lithium chloride (LiCl), calcium chloride (CaCl2) or lithium chloride modified with ethanolamine (E-LiCl).
[0011] Furthermore, the molar ratio of the crosslinking agent to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide is 0.02-0.05:1.
[0012] Furthermore, the cross-linking agent is N,N'-methylenebisacrylamide (MBAA).
[0013] Furthermore, the molar ratio of the initiator to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide is 0.01-0.04:1.
[0014] Furthermore, the initiator is ammonium persulfate or potassium persulfate.
[0015] Furthermore, in step (4), the amount of the initiator-loaded fabric added is 20-40% of the mass of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.
[0016] Furthermore, in step (4), the amount of the initiator-loaded fabric added is 35-40% of the mass of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.
[0017] A gel composite fabric for air water extraction is prepared by the above-mentioned preparation method.
[0018] In the above scheme of the present invention, the hydrogel is a highly water-absorbent porous material with a three-dimensional network structure. The hydrogel material has excellent water absorption performance and can accommodate water tens to hundreds of times its own mass. At the same time, the hydrogel can also effectively retain water and prevent it from being released quickly. In addition, a dynamic coordination can be formed between the hydrogel and the hygroscopic agent, which effectively prevents the leakage of the hygroscopic agent, so that the material exhibits a stable hygroscopic capacity.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the present invention is to load hydrogel in fabric, utilize the presence of hydrogel to enhance the water storage and water retention performance of the material, and improve the adsorption capacity of the material; and through the dynamic coordination between hydrogel and hygroscopic agent, the leakage of hygroscopic agent is effectively prevented, thereby reducing the attenuation of hygroscopic performance of fabric; The gel composite fabric prepared by the method of the present invention not only has a high adsorption capacity but also has a stable moisture absorption performance, and can be widely used in the field of air water extraction. In addition, the preparation method of the present invention does not involve complex equipment, the raw materials are inexpensive, and the process is simple and easy, which is conducive to the market development of air water extraction materials and further expands the application scenarios of fabric materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a scanning electron microscope comparison picture of conventional cotton fabric and the hydrogel composite fabric material prepared by the present invention; Wherein, a is the hydrogel composite fabric material prepared by the present invention, and b is conventional cotton fabric.
[0021] Figure 2 This is a schematic diagram of the principle of the hydrogel composite fabric material prepared by the present invention.
[0022] Figure 3 This is a physical picture of the hydrogel composite fabric material prepared by the present invention.
[0023] Figure 4 This is a comparison diagram of the moisture absorption stability of the hydrogel composite fabric material and the moisture-absorbing fabric prepared by the present invention; wherein a is the actual image after moisture absorption, and b is the cycle stability image. DETAILED DESCRIPTION
[0024] Representative embodiments will now be further refined. It should be understood that the following description is not intended to limit the embodiments to a preferred embodiment. On the contrary, it is intended to cover alternatives, modifications and equivalents that may be included in the essence and scope of the embodiments defined by the appended claims.
[0025] The present invention provides a gel composite fabric for air water extraction; the gel composite fabric is prepared by the following method: (1) First, 1.5-6.0 g of fabric (CF) is ultrasonically treated in a sodium hydroxide solution with a concentration of 20-40 g / L for 1-2 hours, and then the fabric is repeatedly washed with deionized water until it is neutral, and then dried at 70-80 ° C for 8-12 hours to obtain a pretreated fabric; (2) 8.0-14.0 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide (DMAPS), a desiccant and a cross-linking agent are mixed evenly in 100 mL of deionized water, and nitrogen is introduced for treatment for 45-75 minutes to obtain a treatment solution; the amount of the desiccant added is 10-50% of the mass of DMAPS; the desiccant is lithium chloride (LiCl), calcium chloride (CaCl2) or lithium chloride modified with ethanolamine (E-LiCl), etc.; the molar ratio of the cross-linking agent to DMAPS is 0.02-0.05:1; the cross-linking agent is N,N'-methylenebisacrylamide (MBAA); (3) preparing an aqueous solution of a persulfate initiator, and uniformly spraying the aqueous solution of a persulfate initiator on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10-12 hours to obtain an initiator-loaded fabric; the molar ratio of the initiator to DMAPS is 0.01-0.04:1; wherein the initiator is ammonium persulfate or potassium persulfate.
[0026] (4) Immerse the initiator-loaded fabric obtained in step (3) in the treatment solution obtained in step (2), react at 60-70° C. for 8-10 hours, and prepare a gel composite fabric for air water extraction. The amount of initiator-loaded fabric added is 20-40% of the mass of DMAPS, and the ratio is better when it is 35-40%.
[0027] Embodiment 1: The applicant prepared a gel composite fabric for air water extraction through a specific case, and the steps are as follows: (1) First, 4.0 g of CF was ultrasonically treated in a sodium hydroxide solution with a concentration of 30 g / L for 1 hour. The parameters of the cotton fabric were: yarn count 21S, density 30*28; then, the cotton fabric was repeatedly washed with deionized water until neutral, and then dried at 75°C for 8 hours to obtain the pretreated fabric; (2) 11.0 g of DMAPS, desiccant LiCl and cross-linking agent MBAA were mixed evenly in 100 mL of deionized water, wherein the amount of desiccant LiCl added was 27% of the mass of DMAPS, and the molar ratio of cross-linking agent MBAA to DMAPS was 0.05:1; nitrogen was introduced for 45 minutes to obtain a treated solution; (3) preparing an ammonium persulfate initiator aqueous solution according to a molar ratio of initiator to DMAPS of 0.01:1, and spraying the ammonium persulfate initiator aqueous solution uniformly on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10 hours to obtain an initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) in the treatment solution obtained in step (2), wherein the amount of initiator-loaded fabric added is 36% of the mass of DMAPS; reacting at 65° C. for 8 hours to prepare a gel composite fabric material with high moisture absorption and water retention properties.
[0028] The gel composite fabric material has excellent moisture absorption performance, all of which is attributed to the introduction of gel (such as Figure 1 ) and rational design of composite materials (e.g. Figure 2 ).
[0029] Embodiment 2: A gel composite fabric for air water extraction is prepared, and the steps are as follows: (1) First, 4.0 g of CF was ultrasonically treated in a sodium hydroxide solution with a concentration of 30 g / L for 1 hour. The parameters of the cotton fabric were: yarn count 21S, density 30*28; then, the cotton fabric was repeatedly washed with deionized water until neutral, and then dried at 75°C for 8 hours to obtain the pretreated fabric; (2) 11.0 g of DMAPS, desiccant LiCl and cross-linking agent MBAA were mixed evenly in 100 mL of deionized water, wherein the amount of desiccant LiCl added was 27% of the mass of DMAPS, and the molar ratio of cross-linking agent MBAA to DMAPS was 0.05:1; nitrogen was introduced for 45 minutes to obtain a treated solution; (3) preparing a potassium persulfate initiator aqueous solution according to a molar ratio of initiator to DMAPS of 0.01:1, and spraying the potassium persulfate initiator aqueous solution uniformly on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10 hours to obtain an initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) into the treatment solution obtained in step (2), wherein the amount of initiator-loaded fabric added is 36% of the mass of DMAPS; reacting at 65° C. for 8 hours to prepare a gel composite fabric material with high moisture absorption and water retention performance.
[0030] Embodiment 3: A gel composite fabric for air water extraction is prepared, and the steps are as follows: (1) First, 4.0 g of CF was ultrasonically treated in a sodium hydroxide solution with a concentration of 30 g / L for 1 hour. The parameters of the cotton fabric were: yarn count 21S, density 30*28; then, the cotton fabric was repeatedly washed with deionized water until neutral, and then dried at 75°C for 8 hours to obtain the pretreated fabric; (2) 11.0 g of DMAPS, desiccant E-LiCl and cross-linking agent MBAA were mixed evenly in 100 mL of deionized water, wherein the amount of desiccant E-LiCl added was 27% of the mass of DMAPS, and the molar ratio of cross-linking agent MBAA to DMAPS was 0.05:1; nitrogen was introduced for 45 minutes to obtain a treated solution; (3) preparing an ammonium persulfate initiator aqueous solution according to a molar ratio of initiator to DMAPS of 0.01:1, and spraying the ammonium persulfate initiator aqueous solution uniformly on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10 hours to obtain an initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) into the treatment solution obtained in step (2), wherein the amount of initiator-loaded fabric added is 36% of the mass of DMAPS; reacting at 65° C. for 8 hours to prepare a gel composite fabric material with high moisture absorption and water retention performance.
[0031] Embodiment 4: A gel composite fabric for air water extraction is prepared, and the steps are as follows: (1) First, 1.8 g of CF was ultrasonically treated in a sodium hydroxide solution with a concentration of 30 g / L for 1 hour. The parameters of the cotton fabric were: yarn count 40S, density 28*24; then, the cotton fabric was repeatedly washed with deionized water until neutral, and then dried at 75°C for 8 hours to obtain the pretreated fabric; (2) 14.0 g of DMAPS, desiccant LiCl and cross-linking agent MBAA were mixed evenly in 100 mL of deionized water, wherein the amount of desiccant LiCl added was 27% of the mass of DMAPS, and the molar ratio of cross-linking agent MBAA to DMAPS was 0.05:1; nitrogen was introduced for 45 minutes to obtain a treated solution; (3) preparing an ammonium persulfate initiator aqueous solution according to a molar ratio of initiator to DMAPS of 0.01:1, and spraying the ammonium persulfate initiator aqueous solution uniformly on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10 hours to obtain an initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) in the treatment solution obtained in step (2), wherein the amount of initiator-loaded fabric added is 21% of the mass of DMAPS; reacting at 65° C. for 8 hours to prepare a gel composite fabric material with high moisture absorption and water retention performance.
[0032] Embodiment 5: A gel composite fabric for air water extraction is prepared, and the steps are as follows: (1) First, 4.0 g of CF was ultrasonically treated in a sodium hydroxide solution with a concentration of 30 g / L for 1 hour. The parameters of the cotton fabric were: yarn count 21S, density 30*28; then, the cotton fabric was repeatedly washed with deionized water until neutral, and then dried at 75°C for 8 hours to obtain the pretreated fabric; (2) 11.0 g of DMAPS, desiccant LiCl and cross-linking agent MBAA were mixed evenly in 100 mL of deionized water, wherein the amount of desiccant LiCl added was 36% of the mass of DMAPS, and the molar ratio of cross-linking agent MBAA to DMAPS was 0.05:1; nitrogen was introduced for 45 minutes to obtain a treated solution; (3) preparing an ammonium persulfate initiator aqueous solution according to a molar ratio of initiator to DMAPS of 0.01:1, and spraying the ammonium persulfate initiator aqueous solution uniformly on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10 hours to obtain an initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) into the treatment solution obtained in step (2), wherein the amount of initiator-loaded fabric added is 36% of the mass of DMAPS; reacting at 65° C. for 8 hours to prepare a gel composite fabric material with high moisture absorption and water retention performance.
[0033] Comparative Example 1: The preparation method of the material of this comparative example specifically comprises the following steps: 4.0 g of CF was ultrasonically cleaned in 30 g / L NaOH solution for 1 hour, then repeatedly washed with deionized water until neutral, and dried at 75 °C for 8 hours to obtain clean CF.
[0034] Comparative Example 2: The preparation method of the material of this comparative example specifically comprises the following steps: (1) First, 4.0 g of CF was ultrasonically treated in a sodium hydroxide solution with a concentration of 30 g / L for 1 hour. The parameters of the cotton fabric were: yarn count 21S, density 30*28; then, the cotton fabric was repeatedly washed with deionized water until neutral, and then dried at 75°C for 8 hours to obtain the pretreated fabric; (2) Mix 3 g of desiccant LiCl in 100 mL of deionized water and introduce nitrogen gas for 45 minutes to obtain a treated solution; (3) Immersing the pretreated fabric obtained in step (1) in the treatment solution obtained in step (2); reacting at 65° C. for 8 hours to prepare a hygroscopic fabric material.
[0035] The moisture absorption performance of the gel composite fabric of the present invention was tested and compared with that of Comparative Example 1. The results are shown in Table 1 below.
[0036] Table 1 Hygroscopic index measurement results. The measurement process was carried out in accordance with the relevant standards in the national standard "GB / T 41767-2022 Test method for hygroscopicity and equilibrium state adjustment of polymer-based composite materials".
[0037] 25℃, 60% RH (moisture absorption) performance comparison table: Moisture absorption time Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 0 h 0 0 0 0 0 0 1 h 0.45 0.46 0.38 0.37 0.38 0.05 2 h 0.49 0.50 0.40 0.47 0.44 0.06 The moisture absorption (R) of the materials in Table 1 is calculated by the following formula: ; Where M1 is the mass of the composite material after moisture absorption, and M0 is the original mass of the composite material.
[0038] The stability of the gel composite fabric of the present invention was tested and compared with that of Comparative Example 2. The results are shown in Table 2 below.
[0039] Table 2 Moisture absorption index test results. The test process was carried out in accordance with the relevant standards of the national standard "GB / T 9995-1997 Determination of moisture content and moisture regain of textile materials - Oven drying method".
[0040] 105 ℃ stability comparison table: Sample name Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 2 Loss Rate 0.6% 0.4% 0.7% 1.1% 0.7% 47.2 % The material loss rate (S) in Table 2 is calculated by the following formula: ; Where M2 is the dry weight of the composite material after moisture absorption, and M0 is the original dry weight of the composite material.
[0041] As shown in Tables 1 and 2, the results show that the moisture absorption of the hydrogel composite fabric of the present invention is much better than that of pure fabric, and the loss rate is much lower than that of hygroscopic fabric; this indicates that the presence of hydrogel enhances the water storage performance of the material, breaking through the limitation of insufficient moisture absorption of pure fabric. In addition, the coordination effect between the hydrogel and the hygroscopic component effectively prevents the leakage of the hygroscopic agent, increases the effective hygroscopic sites of the material, and helps to achieve rapid moisture absorption and cyclic stability of the material. After ten cycles of moisture absorption and desorption, the moisture absorption capacity of the material has not been significantly attenuated, indicating that the material has excellent cyclic stability (such as Figure 4 ). The comprehensive moisture absorption and stability of the product indicate that the product has excellent moisture absorption and water retention function and cyclic stability. The hydrogel composite fabric of the present invention has good air water absorption effect, and the preparation method is simple and can be mass-produced.
[0042] It is obvious to those skilled in the art that certain modifications, combinations and variations can be made based on the above teachings.
Claims
1. A method for preparing a gel composite fabric for air water extraction, characterized in that: The preparation method specifically comprises the following steps: (1) First, 1.5-6.0 g of fabric is ultrasonically treated in a sodium hydroxide solution with a concentration of 20-40 g / L for 1-2 hours, and then the fabric is repeatedly washed with deionized water until it is neutral, and then dried at 70-80 ° C for 8-12 hours to obtain a pretreated fabric; (2) 8.0-14.0 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide, a hygroscopic agent and a cross-linking agent are mixed evenly in 100 mL of deionized water, and nitrogen is introduced into the mixture for 45-75 minutes to obtain a treated solution; (3) preparing an aqueous solution of a persulfate initiator, and uniformly spraying the aqueous solution of a persulfate initiator on the pretreated fabric obtained in step (1), and then airing the fabric in a ventilated place at room temperature for 10-12 hours to obtain an initiator-loaded fabric; (4) Immersing the initiator-loaded fabric obtained in step (3) in the treatment solution obtained in step (2), reacting at 60-70° C. for 8-10 hours, thereby preparing a gel composite fabric material with high moisture absorption and water retention performance.
2. The preparation method according to claim 1, characterized in that: The desiccant in step (2) is lithium chloride, calcium chloride or lithium chloride modified with ethanolamine.
3. The preparation method according to claim 1, characterized in that: The amount of the desiccant added in step (2) is 10-50% of the mass of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.
4. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of the crosslinking agent to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide is 0.02-0.05:
1.
5. The preparation method according to claim 1 or 4, characterized in that: The cross-linking agent in step (2) is N,N'-methylenebisacrylamide.
6. The preparation method according to claim 1, characterized in that: The molar ratio of the persulfate initiator to [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide is 0.01-0.04:
1.
7. The preparation method according to claim 1, characterized in that: The persulfate initiator is ammonium persulfate or potassium persulfate.
8. The preparation method according to claim 1 or 4, characterized in that: In the step (4), the amount of the initiator-loaded fabric added is 20-40% of the mass of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.
9. The preparation method according to claim 6, characterized in that: In step (4), the amount of initiator-loaded fabric added is 35-40% of the mass of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide.
10. A gel composite fabric for air water extraction, characterized in that: The product is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Medical dressing hydrogel composite fabric as well as preparation method and application thereof
CN103736140A
Preparation method of efficient atmospheric water vapor adsorption composite material
CN116571219A
Composite comprising fabric and polyampholyte hydrogel and preparation method thereof
US20170258571A1
Adaptive polymer hydrogel textile coating
WO2024115246A1